THE EFFECTS OF PROFITABILITY, CAPITAL STRUCTURE, AND FIRM VALUE ON ENVIRONMENTAL (GREEN) ACCOUNTING DISCLOSURE - F. Agung Himawan; Rani Siti Aisyah (ESENSI: Jurnal Manajemen Bisnis, 2024)
This study examines the effects of profitability, capital structure, and firm value on green accounting disclosure among manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2019–2023 and participating in the PROPER program administered by the Ministry of Environment and Forestry (KLHK). Samples were selected using purposive sampling, yielding 41 firms with a total of 205 firm-year observations. The study uses secondary data drawn from annual financial reports over the observation period. Data were analyzed using multiple linear regression. The results show that profitability has a positive and statistically significant effect on green accounting disclosure (at the 1% level). Capital structure has no significant effect on green accounting disclosure. Firm value has a positive and statistically significant effect on green accounting disclosure (at the 5% level).